OPTIMALISASI PENJADWALAN PROYEK JEMBATAN GIRDER GUNA MENCAPAI EFEKTIFITAS PENYELESAIAN DENGAN METODE PERT DAN CPM PADA PT BUANA MASA METALINDO - Taurusyanti, Dewi; Lesmana, Muhamad Fikri (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2015)
ABSTRACTPT Buana Masa Metalindo focuses on providing metal fabrication for various industrial sectors, such asoil, gas, mining, industry and automotive. The current ongoing project is girder bridge. A girder bridge isa high quality light steel frame bridge, which is movable and is very strategic in supporting constructionworks. The issue lies on the project timefram which can be finished in accordance to the time shift set at42 days in the beginning, to 35 days. PERT-CPM method can be utilizied to manage project working timebecome more efficient and effective. In order to reduce the impact of the project delay and cost overruns,three alternative methods can be drawn; (i) additional workforce/labours, (ii) working overtime, and (iii)subcontracting. Acceleration of duration is done on the activities at the critical path and total days thatgiven on each alternative is equaled. Result showed that additional workforces/labours alternativefigured out the optimal time to finish the project which 35 days with projects total cost Rp48,650,000.00.Keyword: effectivity, probability.